2004
DOI: 10.1080/13556210410001717060
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol syndrome in the United States corrections system

Abstract: Prenatal alcohol exposure can result in fetal alcohol syndrome (FAS), which may increase the risk of confinement in the corrections system. In the United States each state and four major cities' corrections systems were asked to complete a questionnaire on the prevalence of FAS and alcohol-related neurodevelopmental disorder (ARND) in the offender population, the availability of screening and diagnostic services to identify offenders with FAS and staff training needs related to FAS. The total population in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 6 publications
1
66
1
2
Order By: Relevance
“…The rates of convicted crimes were similar to the comparison group, and contradict previous studies showing that it is common for adults with FASD to get into trouble with the law. 38 Noteworthy is that a previous report 16 showed that receiving a FAS diagnosis at a younger age may be a protective factor against development of secondary disabilities. In the current study, it should be emphasized that all subjects in the study group had fullblown FAS, whereas none of them had alcohol-related neurobehavioral problems.…”
Section: Discussionmentioning
confidence: 98%
“…The rates of convicted crimes were similar to the comparison group, and contradict previous studies showing that it is common for adults with FASD to get into trouble with the law. 38 Noteworthy is that a previous report 16 showed that receiving a FAS diagnosis at a younger age may be a protective factor against development of secondary disabilities. In the current study, it should be emphasized that all subjects in the study group had fullblown FAS, whereas none of them had alcohol-related neurobehavioral problems.…”
Section: Discussionmentioning
confidence: 98%
“…Significant between-group differences revealed that correctional personnel had significantly lower knowledge and public health nurses had significantly higher knowledge. Relative to correctional personnel, the impact of this lower level of knowledge may be critical as many high-risk individuals have contact with the correctional system (Burd et al 2004;Streissguth et al 1996) and overall prevalence of FASD is higher in correctional settings than in the general population (Burd et al 2004). The cognitive deficits associated with FASD, including impaired judgment, memory problems, and difficulty in planning may contribute to individuals' involvement with the correctional system and limit their ability to follow rules and regulations set forth by this complex system.…”
Section: Differences In General Fas Knowledge and Fas-related Cognitimentioning
confidence: 99%
“…Os efeitos da exposição pré-natal ao álcool foram relatados pela primeira vez por Lemoine et Em uma revisão extensa da literatura, Boland et al 20 sugeriram que a relação entre a FASD e a delinqüência pode Burd et al 26 …”
Section: Revisão Da Literaturaunclassified